Numerical Models in the Epidemiology of Infectious Diseases - Naveed Ul Haq; Sandeep Kumar Tiwari; Pradeep Porwal; Irfan Ul Haq (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The dynamics of infectious disease transmission are subject to fluctuations that are controlled by a number of factors, which must be understood in order to rationally build preventative and control techniques and health policies. In this situation, mathematical modeling can offer helpful insights into patterns of transmission and the identification of parameters to reduce population-wide sickness.